UNVEILING THE REASONING ABILITY OF MODERATELY-SKILLED ELEMENTARY SCHOOL STUDENTS IN LEARNING MATHEMATICS THROUGH THE CONTEXT OF ECO-MATHEMATICS - Prayitno, Sunyoto Hadi; Fiantika, Feny Rita; Hapsari, Dwimartin Bella (UIN Sunan Kalijaga Yogyakarta, 2024)
Mathematical reasoning ability is one of the critical elements of mathematical learning, particularly in solving daily problems and coming to conclusions. Based on preliminary studies, students have difficulty solving mathematical problems, which are difficulty understanding a problem, planning a solution, and concluding a piece of information. Thus, a contextual approach focusing on mathematical objects in daily life's economic and cultural contexts is needed. This study aimed to identify the extent of the mathematical reasoning ability of fifth-grade students in Class V-B of Ketintang 1/409 Elementary School of Surabaya in solving multiplication problems presented in the context of eco-mathematics (economy, culture, object of mathematics). This study applied a qualitative research method with an exploratory, descriptive approach, which describes or depicts a particular phenomenon's condition. Data in the study were collected through written tests, interviews, observations, and documentation. The subjects of this research were students, each of whom had high, medium, and low abilities. The data analysis technique involved credibility testing, dependability testing, confirmability testing, and transferability testing. There are three subjects: high, medium, and low ability. The results of this study indicated that the subjects had moderate abilities during the learning process in the classroom; they were active in answering all questions given by the researchers but still lacked precision. The subjects could explore their learning abilities by discovering new things around them and obtained scores ranging from 39 to 95.